2019
DOI: 10.1039/c9cp01222b
|View full text |Cite
|
Sign up to set email alerts
|

Neutron reflectometry to measure in situ the rate determining step of lithium ion transport through thin silicon layers and interfaces

Abstract: In situ neutron reflectometry experiments found that the interface between silicon and lithium niobate is no significant obstacle for Li permeation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In the case of the 16 nm-thin carbon film, the Li permeability is probably high enough to transport all incoming Li into the film interior, whereas for the thicker carbon film, the Li permeability is lower and only the surface near region is lithiated. This may indicate a higher Li permeability of carbon material in thinner films, as it was measured for amorphous silicon material in thin layers [49,50].…”
Section: Electrode With Carbon Films: Differential Charge and Capacit...mentioning
confidence: 56%
“…In the case of the 16 nm-thin carbon film, the Li permeability is probably high enough to transport all incoming Li into the film interior, whereas for the thicker carbon film, the Li permeability is lower and only the surface near region is lithiated. This may indicate a higher Li permeability of carbon material in thinner films, as it was measured for amorphous silicon material in thin layers [49,50].…”
Section: Electrode With Carbon Films: Differential Charge and Capacit...mentioning
confidence: 56%
“…Diffusion coefficients and activation energies for self-diffusion have been obtained with NR in a variety of materials. In nonoxide high-temperature superhard ceramic coatings, nitrogen self-diffusion was measured in amorphous Si 3 N 4 , and in silicon carbo-nitrides. , For crystalline metal oxides, lithium self-diffusion was examined in LiNbO 3 . , Self-diffusion was measured in metals such as in nanocrystalline copper, iron, , and Fe-based compounds .…”
Section: Introductionmentioning
confidence: 99%
“…The most common technique is the tracer method, which tracks the spatial distribution of isotopic elements at different times under the isothermal condition with different techniques, including secondary ion mass spectrometry (SIMS). Using nuclear magnetic resonance (NMR) or quasi-elastic neutron scattering (QENS) makes it possible to analyze atomic diffusion in crystalline materials and in battery research. Diffusion coefficients of atomic diffusion have also been measured by low-angle X-ray diffraction (XRD) (X-ray reflectometry, XRR) in solids, , XRD, , energy-dispersive X-ray spectroscopy, ,, and low-angle neutron diffraction (neutron reflectometry, NR). Most studies reported in the literature have been based on the isothermal condition, which require multiple measurements at different temperatures in order to determine the activation energy for atomic diffusion in solids. For example, Mizoguchi and Murata conducted low-angle XRD (XRR) analysis of compositionally modulated amorphous Co–Zr films isothermally annealed consecutively at different temperatures in a range of 120–180 °C and calculated the activation energy for the interdiffusion in the modulated amorphous Co–Zr films from the variation of the intensity of the X-ray peak.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations